2018
DOI: 10.1097/ijg.0000000000001010
|View full text |Cite
|
Sign up to set email alerts
|

Four Questions for Every Clinician Diagnosing and Monitoring Glaucoma

Abstract: We pose 4 questions for the clinician diagnosing and monitoring glaucoma, and supply evidence-based answers. The first question is: "When do you perform a 10-2 (2-degree grid) visual field (VF) test?" We argue the best answer is: anyone you would do, or have done, a 24-2 (6-degree grid) VF on should have both a 24-2 and a 10-2 VF within the first 2 visits. Second, "When do you perform an optical coherence tomography (OCT) scan of the macula?" We argue that, if you are performing an OCT test, then it should inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 32 publications
3
22
0
2
Order By: Relevance
“…First, the sample size of 53 glaucomatous and 45 healthy control eyes, involved in the development and evaluation of the new method, is relatively small. Nonetheless, the results of this study agree with a previous qualitative analysis of a different data set of a similar nature, 2 and the results from the validation group of 101 eyes showed excellent agreement. The age difference between the two groups (i.e., DG and H eyes) is also not desirable, mainly in diagnostic studies, although ours is not.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…First, the sample size of 53 glaucomatous and 45 healthy control eyes, involved in the development and evaluation of the new method, is relatively small. Nonetheless, the results of this study agree with a previous qualitative analysis of a different data set of a similar nature, 2 and the results from the validation group of 101 eyes showed excellent agreement. The age difference between the two groups (i.e., DG and H eyes) is also not desirable, mainly in diagnostic studies, although ours is not.…”
Section: Discussionsupporting
confidence: 90%
“…Using a reference database from the OCT device manufacturers (data provided by Topcon, Inc.), we generated age-corrected deviation/probability maps, as previously described and employed in an established OCT widefield report. 6 The reference database included eyes with (1) normal 24-2 VFs (abnormal defined as Glaucoma Hemifield Test "outside normal limits" and/or Pattern Standard Deviation (PSD) <5%), (2) no eye pathology, and (3) intraocular pressure lower than 21 mm Hg. The The RGC+ and RNFL probability plots, respectively, with the 24-2 and 10-2 locations superimposed as large (24-2) and small (10-2) circles.…”
Section: Structural (Oct) Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In any case, if structural damage does precede functional damage, then a clinical comparison between a VF (functional) test and an OCT (structural) test may be of questionable value, at least in the case of early damage. However, we5,7 and others6,8 have argued that the extent to which structural and functional glaucomatous damage agree depends upon various factors, such as the particular test and test measures used, and the baseline conditions for a particular patient. In addition, structural damage, as measured by OCT retinal nerve fiber layer (RNFL) thickness, and functional damage, as measured with VFs, parallel each other, often in a linear fashion 5,9.…”
mentioning
confidence: 96%
“…Chen et al showed that if two points were added to the superior macular region of the Humphrey 24-2 pattern, it increased the number of abnormal locations G in individuals with glaucoma 10 . Thus, clinicians should be aware of the limitations of the 24-2 in the presence of suspicious discs and "normal" visual fields 11 .…”
mentioning
confidence: 99%